The role of cellular senescence in skin aging and age-related skin pathologies - Chin, Toby; Lee, Xin Er; Ng, Pei Yi; Lee, Yaelim; Dreesen, Oliver (Frontiers in Physiology, 2023)
Aging is the result of a gradual functional decline at the cellular, and ultimately, organismal level, resulting in an increased risk of developing a variety of chronic illnesses, such as cardiovascular disease, stroke, cancer and diabetes. The skin is the largest organ of the human body, and the site where signs of aging are most visible.These signs include thin and dry skin, sagging, loss of elasticity, wrinkles, as well as aberrant pigmentation. The appearance of these features is accelerated by exposure to extrinsic factors such as ultraviolet (UV) radiation or pollution, as well as intrinsic factors including time, genetics, and hormonal changes. At the cellular level, aging is associated with impaired proteostasis and an accumulation of macromolecular damage, genomic instability, chromatin reorganization, telomere shortening, remodelling of the nuclear lamina, proliferation defects and premature senescence.Cellular senescence is a state of permanent growth arrest and a key hallmark of aging in many tissues. Due to their inability to proliferate, senescent cells no longer contribute to tissue repair or regeneration. Moreover, senescent cells impair tissue homeostasis, promote inflammation and extracellular matrix (ECM) degradation by secreting molecules collectively known as the "senescence-associated secretory phenotype" (SASP). Senescence can be triggered by a number of different stimuli such as telomere shortening, oncogene expression, or persistent activation of DNA damage checkpoints. As a result, these cells accumulate in aging tissues, including human skin. In this review, we focus on the role of cellular senescence during skin aging and the development of age-related skin pathologies, and discuss potential strategies to rejuvenate aged skin.